The Linguistic Expression of Animal Thinking: Answering Philosophical Objections - Crelier, Andrés (Analysis. Journal of Philosophical Research, 2020)
The article puts forward the thesis that it is possible in principle to express the content of animal thinking by means of a natural language. Firstly, I propose an interpretation of the research in the current cognitive ethology as making scientific progress, and I argue that this progress presupposes a possible linguistic expression of the animal thoughts (i); secondly, I try to weaken certain objections to the main thesis of the article, regarding the impossibility of grasping non-conceptual and no-familiar contents (ii); thirdly, I use the distinction between expressing and describing a thought (Dennett) to show how the linguistic expression of animal thoughts can be carried out (iii).